Pencitraan Kekerasan Saddam Hussein Terhadap Perempuan Sebagai Propaganda Amerika Serikat - Dewi, Machya Astuti (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
Through internet, the United States has been shaping public opinion by the way of presenting Saddam Hussein as regime who commits a violent against women. This case indicated that gender issue gains more significance in international politics.